Legal Protection for Consumers of Syrup Drugs Causing Atypical Progressive Acute Kidney Failure (GGGAPA) in Children: Analysis Based on Law Number 8 of 1999 - Ahmad Muchlasin Nur Ihsan; Diana Setiawati (Universitas Muhammadiyah Surakarta, 2023)
Human life from ancient times until now will never be separated from health products to help accelerate the healing of illnesses experienced by humans. Many kinds of medicinal products are made by manufacturers from traditional medicines that use natural ingredients and drugs that use chemicals as a mixture. Drugs that use chemicals if their use is not in accordance with existing requirements will cause health problems ranging from kidney failure to death. So consumer protection here is very important, so that people who feel their rights and interests are harmed by consuming these products, and ensure legal certainty for consumers to get legal protection. The purpose of this study is to determine consumer protection in cases of acute kidney failure in children who are suspected of consuming syrup medicine in accordance with Law Number 8 of 1999 concerning Consumer Protection, and to analyze the government's role in handling this case. This study uses normative research methods. Sources of data in this study used primary and secondary data, through interviews, and literature studies. This study aims to determine the government's role in protecting consumers in cases of acute kidney failure caused by syrup drugs, namely by imposing penalties on business actors to provide compensation to victims who experience acute kidney failure, as well as withdrawing drugs identified as the cause. acute kidney disease.